The Role of Government and Citizens in Creating a Healthy and Prosperous Life in Serdang Village, Beringin District - Yuli Simatupang; Muammar Risky Rangkuti; Nurika Kholila Pohan; Sera Harmiati Br Ginting; Siti Nur Diah; Susianti Tampubolon; Fauzan Hilmi Dani Lubis (Indonesian Journal of Society Development, 2022)
The purpose of this study was to find out how the community participates in creating a healthy and prosperous life, especially in participating in every government program in implementing family planning, stunting prevention, posyandu, and the elderly in Serdang Village, Beringin District, Deliserdang Regency. The type of research used by the authors in this study is qualitative with the method of documentation study and also in-depth interviews. The results of this study indicate that the Village Head and Head of the UPT Population Control Family Planning for Women's Empowerment and Child Protection (PPKBP3A) of Beringin District have provided information to the community through employees and village midwives in the form of socialization or counseling regarding the family planning program, although they still have problems in its implementation. However, it was found that the villagers had not actively participated in improving and realizing sustainable development, namely the goal of a healthy and prosperous life. To increase community participation, a theory is needed according to Bintoro Tjokroamidjojo which consists of three important elements, namely (1) Leadership Issues, (2) Communication, and (3) Education